ChemInform Abstract: Hydrido‐Cobalt Catalyst as a Selective Tool for the Dimerization of Arylacetylenes: Scope and Theoretical Studies. Issue 14 (8th April 2014) - Ventre, Sandrine; Derat, Etienne; Amatore, Muriel; Aubert, Corinne; Petit, Marc
Abstract The dimerization of arylacetylenes in the presence of the hydrido‐cobalt complex proceeds with high regio‐ and stereoselectivity to produce (E)‐1, 4‐enynes in excellent yield.